Numerical study of Newtonian fluid flows in T-shaped structures with impermeable walls - Pepe (2019)
This article presents the results of flows in "T" shaped duct bifurcations. The problem is to find the resistance to flow in three-dimensional (3D) structures with different homothetic relationships between sizes (diameters and lengths) of parent and daughter ducts. The method used is the Constructal Design, which is based on the Constructal Theory. The minimization of the global resistance to flow, subjected to geometric constraints of volume and area occupied by the ducts, is the key to search for optimum configurations. The flows investigated were three-dimensional, laminar, incompressible, in steady state, with uniform and constant properties. The results obtained numerically were verified via comparison with analytical results available in the literature. In this work, ranges of length and ratio of diameterss from 0.5 to 1 and 0.1 to 1, respectively, were investigated, for Reynolds numbers equal to 102 and 103. The main results indicate that the T-shaped structure with impermeable walls, agree with Hess-Murray's law.